Kepemimpinan Transformasional Kepala Sekolah Dalam Meningkatkan Mutu Pendidikan Pada SDN 2 Bungai Jaya Kecamatan Basarang Kabupaten Kapuas - L Laliana; Ade Hermawan (STIA Bina Banua Banjarmasin, 2020)
This type of research is a qualitative descriptive study with a research location in Basarang District, Kapuas Regency, Central Kalimantan. Data collection techniques used in this study were interviews, observation, and documentation. The informants in this study were farmers in Basarang Subdistrict, Kapuas Regency, Central Kalimantan, which consisted of Balinese and Javanese. As for the key informants in this study are those who know firsthand about how the work culture of farmers in the transmigrant community in improving agricultural productivity, namely the village heads in the Basarang District, Kapuas Regency, Central Kalimantan. Based on the results of the study note that: 1) The application of the work culture values ​​of transmigrant farmers in the District of Basarang Kapuas District has been implemented well, the values ​​of work culture that are applied, among others: a) Discipline, namely behavior that always rests on the rules and norms that apply within and outside the company or the community environment. Discipline includes compliance with laws and regulations, procedures, interacting with partners, and so on; b) Openness, which is the readiness to give and receive true information from and to fellow partners or the community for the common good; c) Mutual respect, which is a behavior that shows respect for individuals, duties and responsibilities of other fellow partners or the community; d) Cooperation, namely the willingness to give and receive contributions from and or to partners in achieving common goals and targets. 2) Aspects that have an influence on the success of farmers in transmigrant communities in Basarang District, Kapuas Regency, Central Kalimantan, include: a) Motivation has an influence on the success of farmers in transmigrant communities in Basarang District, Kapuas Regency. A high work culture is influenced by high motivation. Work culture makes a view and attitude based on values ​​believed by someone. This belief is the motivation for work; b) Environmental/geographical conditions, making the work culture of transmigrant farmers' communities emerge due to the environment that supports people in doing business to be able to manage and benefit, and can even invite pandatang to participate in making a living in that environment. Berdasarkan hasil penelitian diketahui bahwa: 1) Kepemimpinan kepala sekolah SDN 2 Bungai Jaya merupakan tipe pemimpin transformasional yang memiliki empat komponen seperti: konsiderasi pribadi, stimulasi intelektual, motivasi inspirasional, dan idealisasi pengaruh. Dalam praktik kepemimpinannya, kepala sekolah menjadi figur yang patut dijadikan teladan, menjadi seorang inspritor bagi sekolah. Senantiasa memotivasi dan mendorong bawahannya untuk selalu berinovasi, bekerja keras dan bersikap profesional dalam menjalankan tugas dan kewajiban. Mengajak bawahannya untuk mampu berpikir dengan cara-cara yang baru dalam setiap kegiatan sekolah. Berani merubah status quo untuk kepentingan meningkatkan mutu pendidikan yang lebih baik, senantiasa menumbuhkan loyalitas dan antusiasme dengan penegakan disiplin dan pola penggerakan bawahan berdasarkan kesadaran dalam meningkatkan mutu pendidikan. 2) Perubahan yang dilakukan kepala sekolah yakni di bidang kurikulum, kesiswan, personalia, sarana prasarana, dan hubungan sekolah dengan masyarakat. Proses pengambilan keputusan yang dilaksanakan dilaksanakan secara demokratis. Pengambilan keputusan dilakukan melalui tahapan-tahapan: identifikasi masalah, pengumpulan dan analisa data, pembuatan alternatif keputusan dengan melibatkan semua warga sekolah; proses komunikasi yang dilakukan kepala sekolah berjalan secara efektif dan efisien. Jalur yang digunakannya tidak hanya bersifat formal saja seperti lewat rapat dinas sekolah atau surat edaran, tetapi juga menggunakan jalur non-formal, lewat obrolan-obrolan saat santai di ruang guru waktu jam istirahat. Untuk memperoleh dukungan cara yang dilakukan adalah dengan melibatkan seluruh unsur yang ada disekolah untuk memberikan masukan sehingga muncul sikap peduli dan tanggungjawab terhadap keputusan dan dilibatkan dalam pembuatan keputusan tersebut.